2019
DOI: 10.12928/jehcp.v8i1.12195
|View full text |Cite
|
Sign up to set email alerts
|

The Positive Impact of Organizational Trust: a Systematic Review

Abstract: The critical role of trust is to strengthen working relationships to ensure that organizations achieve their goals effectively. This study aims to explore the positive impact of organizational trust, namely trust towards colleagues, employers, and organization. We conducted a systematic review following the PRISMA guideline, highlighting the number of records that were identified, screened, assessed for eligibility, and included for the study. The literature search was conducted online by using the keyword "Or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 15 publications
0
7
1
Order By: Relevance
“…Employee trust in the organization is determined by the confidence of employees in their colleagues and leaders. In this case the leader has a big role to be able to increase employee confidence in the organization (Rahayuningsih, 2019). Rua and Araújo (2016) in the study found that there was a correlation between leadership and organizational trust.…”
Section: Leadership and Organizational Trustmentioning
confidence: 90%
See 1 more Smart Citation
“…Employee trust in the organization is determined by the confidence of employees in their colleagues and leaders. In this case the leader has a big role to be able to increase employee confidence in the organization (Rahayuningsih, 2019). Rua and Araújo (2016) in the study found that there was a correlation between leadership and organizational trust.…”
Section: Leadership and Organizational Trustmentioning
confidence: 90%
“…al. (2012), Uslu and Oklay (2015), Rahayuningsih (2019), Rua and Araújo (2016) which concluded that there is a direct influence of leadership on organizational trust.…”
Section: H2: There Is a Positive Direct Effect Of Leadership Effectivmentioning
confidence: 99%
“…If employees have trust in their organization, they join more constructive behaviors and exert efforts to support their organization to meet organizational success (Rahman et al, 2021). Parallel findings have been discussed that organizational trust can decrease turnover tendency, and improves effective communication, innovative behaviors, job satisfaction, motivation, and work performance among employees (Rahayuningsih, 2019). Social learning theory (SLT) well illustrates the relationship between ethical leadership and employee trust (Yu et al, 2018).…”
Section: Hypotheses Development Ethical Leadership and Organizational...mentioning
confidence: 97%
“…The Concept of Professional Attitude The military profession can be called a profession with a class of public goods that is different from the profession of doctors and lawyers belonging to the profession of private goods [4]. The professional military is a picture of the military that has expertise specifications in the field of defense, has a social responsibility that is serving the country or in other words pays attention to national interests, and has a corporate character that gives birth to strong Esprit De Corps [12].…”
Section: Ii2mentioning
confidence: 99%
“…Performance indicators can also be defined as certain values or characteristics that are used to measure the output or outcome of an activity. Whereas [12] states that in accordance with the notion of performance that is what is done or not done by an employee in carrying out his main tasks, the performance indicators in carrying out work in an organization or company environment includes five elements, namely: (a) Quantity of results work achieved, (b) The quality of the work achieved, (c) The time period for achieving the performance, (d) Attendance and activities while present at work, and (e) Ability to work together.…”
Section: Ii4 the Concept Of Personnel Performancementioning
confidence: 99%